Circus Women of the Late 19th and Early 20th Centuries in Argentina. Tent Life between Freedom and Resistance - Camila Losada (telondefondo. Revista de Teoría y Crítica Teatral, 2021)
This work aims to analyze the representations of female circus artists between the late 19th and early 20th centuries in Argentina, focusing on the tensions that configured their sex-generic identities and corporalities and on their dissonant ways of acting femininity, moreover, recovering and putting in value circus knowledge and practices that have been historically invisible from a gender perspective. Using archive material, testimonies and interviews, I reflect on the paradoxical intersection between patriarchal mandates and the spaces of freedom and resistance that the circus enabled for women, becoming challenging models for the time, in a context in which a conservative morality operated repressing sexuality and bodies and was beginning to be disputed by women and the first steps of feminism.